2018
DOI: 10.3390/f9120742
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa and Climate Change: Insights from Smallholder Cocoa Producers in Ghana Regarding Challenges in Implementing Climate Change Mitigation Strategies

Abstract: This study investigates the knowledge and perception of smallholder cocoa farmers on the potential impacts of climate change on cocoa production in Ghana. It addresses opinions on the inclusion of climate change mitigation strategies (such as Reducing Emissions from Deforestation and Forest Degradation—REDD+) into cocoa production, and potential obstacles and roles of stakeholders in ensuring community acceptance of such strategies in a unique multiple land use area—the Krokosua Hills Forest Reserve. Data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…Among the abiotic stress, drought stress is one of the key constraints to the establishment and productivity of cocoa trees (Djan et al, 2018;Gateau-Rey et al, 2018;Schroth, Läderach et al, 2016;Suzuki et al, 2014). This assertion has been confirmed in Ghana (Ameyaw et al, 2018;Hutchins et al, 2015), Nigeria (Agbongiarhuoyi et al, 2013); Trinidad and Tobago (Eitzinger et al, 2015) and Costa Rica (Deheuvels et al, 2012;Hutchins et al, 2015;Phillips, 2015), in surveys of cocoa farmers that were intended to assess the relative effects of climatic change on the productivity of cocoa. For instance, Ameyaw et al (2018) assessment of cocoa farmers knowledge and perception of climate change impact on cocoa production in Ghana found that, out of the 205 farmers interviewed, 89% and 81 % mentioned reduction in the amount of rainfall and reduced length of the wet season as major constraints, in addition, 81% of the farmers indicated that dry spells (drought) had increased.…”
Section: Effect Of Water Stress (Drought) On Cocoa Tree Growth and Productivitymentioning
confidence: 89%
“…Among the abiotic stress, drought stress is one of the key constraints to the establishment and productivity of cocoa trees (Djan et al, 2018;Gateau-Rey et al, 2018;Schroth, Läderach et al, 2016;Suzuki et al, 2014). This assertion has been confirmed in Ghana (Ameyaw et al, 2018;Hutchins et al, 2015), Nigeria (Agbongiarhuoyi et al, 2013); Trinidad and Tobago (Eitzinger et al, 2015) and Costa Rica (Deheuvels et al, 2012;Hutchins et al, 2015;Phillips, 2015), in surveys of cocoa farmers that were intended to assess the relative effects of climatic change on the productivity of cocoa. For instance, Ameyaw et al (2018) assessment of cocoa farmers knowledge and perception of climate change impact on cocoa production in Ghana found that, out of the 205 farmers interviewed, 89% and 81 % mentioned reduction in the amount of rainfall and reduced length of the wet season as major constraints, in addition, 81% of the farmers indicated that dry spells (drought) had increased.…”
Section: Effect Of Water Stress (Drought) On Cocoa Tree Growth and Productivitymentioning
confidence: 89%
“…Farmers' perceptions of ongoing climatic changes in Ghana did not match scientists' understanding based on historical weather records, impacting their willingness to participate in conservation programs [22].…”
Section: Temporalmentioning
confidence: 99%
“…This is often connected to an epistemological understanding that different knowledge types exist and that people can have different perceptions on the same aspect of ecosystem service delivery [71]. A common mismatch is between Western science knowledge and either people's perceptions, or other knowledge systems, such as local and traditional ecological knowledge [22]. This mismatch exists not only between Western science and indigenous communities, which often have their own knowledge systems (e.g., indigenous medicine), but also between Western science and other Western knowledge systems (e.g., farmers in Western, industrialized countries).…”
Section: Functional-conceptual Mismatchesmentioning
confidence: 99%
“…Generally, climate change models predict reduced rainfall, increased light intensity, and higher temperatures. These changes will have significant limitations to cocoa production in the near future, with some areas of West Africa already being affected according to Läderach et al [17] and Hutchins et al [73]. These studies contend that longer periods of drought and higher temperatures are causing fluctuations in cocoa productivity and death, hence, recommend that farmers develop resilient shade-grown cocoa systems, as it is believed that shade trees play a key role in regulating light intensity, humidity, and temperature, and provide green waste for soil nutrient improvement [28,66,74].…”
Section: Consequences Of Unshaded Cocoa Agroforestry Regimes On the Environmentmentioning
confidence: 99%